IDDAH PROVISIONS IN ISLAMIC JURISPRUDENCE(GENDER PERSPECTIVE) - Burhanuddin (Journal of Islamic Religious Studies, 2024)
This research aims to find answers to iddat for women in Islamic jurisprudence, followed by iddat for husbands in fiqh literature, from a gender perspective. In this study, the researcher used a literature review method, with a qualitative descriptive approach. Iddat is a consequence of divorce, which occurs when love turns into hatred, anger, disappointment, and so on. This often leads to quarrels culminating in divorce or talak. Despite divorce being highly disliked by Allah SWT, the principle of marriage in Islam is to establish relationships for an indefinite period. The terminology of iddat existed before the advent of Islam, but the practice of iddat at that time was highly inhumane. In Islamic legal sources, iddat is considered an obligation that must be fulfilled by women. When analyzed through a gender lens, it is clear that iddat discriminates against women when husbands are not subjected to it, as women equally contribute to the advancement of religion and the state. In essence, iddat for husbands has been introduced by scholars in fiqh literature, albeit limited to two conditions. Therefore, fiqh, as a representation of Islamic law, needs to be reviewed to be in synergy with the social conditions of society. This is in line with the principle that legal changes are caused by changing situations and conditions. While the implementation of iddat for husbands currently applies generally, it is a primary necessity with two balanced benefits, both vertical and horizontal. Considering that iddat for husbands is not clearly covered in Islamic legal sources, the normative basis (the Quran and Hadith) used is the universal aspect of meaning contained in both sources.